PENGERTIAN, PERANAN, DAN FUNGSI KURIKULUM - Elisa Elisa (Universitas Quality, 2018)
Curriculum is something that is planned as a guide to achieve the goal of education. What is usually planned is an idea, an aspiration of human beings or citizens that will be formed. What can be realized is called real curriculum,meanwhile, which can not be realized,in fact,is still an idea.The 2013 curriculum is simplified and thematic-integrative curriculum, whichits school hours are added.It is intended to encourage learners or studentstohave better ability to make observations, to ask questions, to do reasoning, and to communicate (to present) what theyget or know after learning lesson materials, and to make our students to have attitude competencies, skills, and much better knowledge. They will be more creative, innovative, and more productive, so that they can be successful in dealing with various problems and challenges in his day later, and have a better future.